Dietary shochu kasu alleviates fatty liver induced by orotic acid - Yohanes Buang; Pius D. Ola; Teruyoshi Yanagita (Bangladesh Pharmacological Society, 2010)
The effects of dietary shochu kasu (5%) on orotic acid-induced fatty liver were studied in rats. Liver triglyceride content of orotic acid-fed rats increased by 5-fold in comparison to basal group.  Shochu kasu reduced triglyceride content by two-third.  The activities of fatty acid synthase and phosphatidate phosphohydrolase significantly decreased that was approximately by 35% and 20%, respectively. The serum lipid levels however were nearly unchanged. The alleviation of fatty liver in rats with shochu kasu, therefore, was associated with the inhibition of fatty acid synthase and phosphatidate phosphohydrolase activities.